Immune Checkpoint Inhibitors and CAR-T Cell Therapy: Thrombotic and Vascular Complications - Udvardy, Miklós (Archives of Clinical and Biomedical Research, 2025)
Background: Due to the different genetic properties of malignant neoplasms and their tendency to cause the formation of blood clots, the risk of these complications is much higher than in the general population. There is even a higher risk of blood clots forming during chemotherapy or hormone therapy for cancer. Aim: This paper will summarise publications to gain a better understanding of the risks of blood clots associated with checkpoint inhibitors and CAR-T cell therapy of cancer. The review will also address potential problems and guide how to address them. Even when used on their own, checkpoint inhibitors can cause blood clots, albeit at a lower rate than chemotherapy; however, this assumption has not been definitively proven, as ICI-type agents are rarely given to cancer patients as monotherapy (or if given, these cancers baseline thrombogenicity is less active sui generis). The incidence of these problems varies depending on the type of disease, patient characteristics and somewhat on immunotherapeutic drug selection itself. It is important to inform doctors who prescribe these treatments of this fact and try to provide ideas which may help make good individual decisions. The anticoagulant prophylaxis is probably indicated in many such cases, even with monotherapy in cancer. However, still on a somewhat individual basis, as prospective, multicentre, double blind trials are not available, recommendations are based on some rather anecdotal, or retrospective data in respect of disease type, treatment and patient characteristics and the selection of an optimal anticoagulant prophylactic approach.